2005
DOI: 10.1111/j.1365-294x.2005.02454.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of annual and perennial populations ofZostera marinaL. along the Pacific coast of Baja California and the Gulf of California

Abstract: The Baja California peninsula represents a biogeographical boundary contributing to regional differentiation among populations of marine animals. We investigated the genetic characteristics of perennial and annual populations of the marine angiosperm, Zostera marina, along the Pacific coast of Baja California and in the Gulf of California, respectively. Populations of Z. marina from five coastal lagoons along the Pacific coast and four sites in the Gulf of California were studied using nine microsatellite loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 74 publications
6
58
0
1
Order By: Relevance
“…While this will promote strong differentiation at the local scale, connectivity among patchesby incoming dispersal from rafted, fertile seeds -neutralizes this effect. Similar examples of locally high F IS have been found in other European (Olsen et al 2004) and Pacific-Mexican populations (Muniz-Salazar et al 2005) of Z. marina. Alternative explanations for elevated F IS values, such as null alleles, have been ruled out by extensive analyses (Olsen et al 2004), and Wahlund effects, though never completely ruled out, seem unlikely here given, the level of population differentiation observed.…”
Section: High Standing Variation and Clonal Diversitysupporting
confidence: 81%
“…While this will promote strong differentiation at the local scale, connectivity among patchesby incoming dispersal from rafted, fertile seeds -neutralizes this effect. Similar examples of locally high F IS have been found in other European (Olsen et al 2004) and Pacific-Mexican populations (Muniz-Salazar et al 2005) of Z. marina. Alternative explanations for elevated F IS values, such as null alleles, have been ruled out by extensive analyses (Olsen et al 2004), and Wahlund effects, though never completely ruled out, seem unlikely here given, the level of population differentiation observed.…”
Section: High Standing Variation and Clonal Diversitysupporting
confidence: 81%
“…Measures of genetic diversity offer an alternative for the assessment of conservation value in seagrass habitats [43]; results provided here closely match a growing trend in which eelgrass populations are shown to be more genetically diverse than anticipated [17,29,41]. Two similar studies [40,44] empirically tested the role of genetic diversity in a seagrass population's ability to recover from disturbances.…”
Section: Discussionsupporting
confidence: 53%
“…In analyses of microsatellite loci, awareness of the effect null alleles may have upon results is worthwhile [39]. Like most foundational studies on eelgrass genetics [13,29,40,41], an estimate of null alleles was not employed here. In one study that did estimate the effect of null alleles, Campanella et al [30] found little influence by null alleles upon computed -statistics.…”
Section: Plotmentioning
confidence: 99%
“…This was not the case. Although only qualitative comparisons of mean  can be made due to differences in normalization and the number of loci used across studies, the mean of 4.78 (Table 1) for the southern California mainland populations is within the estimates of  for Z. marina populations along the US Pacific coast, i.e., San Juan Is, WA (2.74; Wyllie-Echeverria et al, 2010), Bodega Bay, CA (5.81; Olsen et al, 2004), San Francisco Bay (4.29; Ort et al, 2012), and Baja California, Mexico (4.74;Muniz-Salazar et al, 2005). In the global context, where >150 locations have been surveyed worldwide, the highest diversities found with these loci have been in (Pritchard et al, 2000).…”
Section: A Closer Look At Diversitysupporting
confidence: 55%